Selective Ablation of Ctip2/Bcl11b in Epidermal Keratinocytes Triggers Atopic Dermatitis-Like Skin Inflammatory Responses in Adult Mice - Wang, Zhixing (Public Library of Science, 2012)
BACKGROUND: Ctip2 is crucial for epidermal homeostasis and protective barrier formation in developing mouse embryos. Selective ablation of Ctip2 in epidermis leads to increased transepidermal water loss (TEWL), impaired epidermal proliferation, terminal differentiation, as well as altered lipid composition during development. However, little is known about the role of Ctip2 in skin homeostasis in adult mice. METHODOLOGY/PRINCIPAL FINDINGS: To study the role of Ctip2 in adult skin homeostasis, we utilized Ctip2(ep−/−) mouse model in which Ctip2 is selectively deleted in epidermal keratinocytes. Measurement of TEWL, followed by histological, immunohistochemical, and RT-qPCR analyses revealed an important role of Ctip2 in barrier maintenance and in regulating adult skin homeostasis. We demonstrated that keratinocytic ablation of Ctip2 leads to atopic dermatitis (AD)-like skin inflammation, characterized by alopecia, pruritus and scaling, as well as extensive infiltration of immune cells including T lymphocytes, mast cells, and eosinophils. We observed increased expression of T-helper 2 (Th2)-type cytokines and chemokines in the mutant skin, as well as systemic immune responses that share similarity with human AD patients. Furthermore, we discovered that thymic stromal lymphopoietin (TSLP) expression was significantly upregulated in the mutant epidermis as early as postnatal day 1 and ChIP assay revealed that TSLP is likely a direct transcriptional target of Ctip2 in epidermal keratinocytes. CONCLUSIONS/SIGNIFICANCE: Our data demonstrated a cell-autonomous role of Ctip2 in barrier maintenance and epidermal homeostasis in adult mice skin. We discovered a crucial non-cell autonomous role of keratinocytic Ctip2 in suppressing skin inflammatory responses by regulating the expression of Th2-type cytokines. It is likely that the epidermal hyperproliferation in the Ctip2-lacking epidermis may be secondary to the compensatory response of the adult epidermis that is defective in barrier functions. Our results establish an initiating role of epidermal TSLP in AD pathogenesis via a novel repressive regulatory mechanism enforced by Ctip2.